When and How to Adjust Beyond the Business Cycle? : A Guide to Structural Fiscal Balances - Bornhorst, Fabian (Technical Notes and Manuals; Technical Notes and Manuals ;, 2011)
Technical Notes and Manuals are produced by IMF departments to expand the dissemination of their technical assistance advice. These papers present general advice and guidance, drawn in part from unpublished technical assistance reports, to a broader audience. This new series was launched in August 2009.